Policy Adoption of Forest Management Unit: A Knowledge Diffusion Analysis - Julijanti Julijanti; Bramasto Nugroho; Hariadi Kartodihardjo; Dodik Ridho Nurrochmat (Institut Pertanian Bogor (IPB University), 2014)
Within the policy adoption process of Forest Management Unit (FMU) concept, there has been disagreement of stakeholders on FMUs concept. This disagreement is caused by the exchange of knowledge, information, and perception among stakeholders involved. The results of these interactions could speed up, slow down, and prevent the adoption process of FMU policy. The study objective was analyzing process of knowledge diffusion of FMUs development policy and stakeholders interaction in PFMU Batutegi and PFMU Kotaagung Utara, Indonesia. Adoption process was analyzed by the logical diffusion technique based on knowledge time of FMUs concept received and its interaction space. Social interaction among stakeholders was analyzed using method developed by International Development Studies analysis, i.e. interaction among discourse/narrative, actors/networks and politics/interests. The results showed that knowledge diffusion of FMUs concept in both PFMU tends to cascade diffusion. Factors was affecting of it process were network, role of opinion leaders, willingness to know, and understand on FMUs concept. Indicative strategy is needed as anticipating and overcoming an obstacle in its internalization process, i.e. harmonization of legislative and executive relationship, building an opinion the importance of FMU, and optimalizing network for bureaucratic problems.